Lectotypification of Uropetalon concanense (Asparagaceae): An endemic species from Western Ghats, India - Deshpande, Anup S.; Krishnan, S.; Janarthanam, M. K. (Rheedea, 2015)
The name Uropetalon concanense Dalzell [=Dipcadi concanense (Dalzell) Baker] is lectotypified here.